Discovery of Potential Anti-infective Therapy Targeting Glutamine Synthetase in Staphylococcus xylosus - Cui, Wen-Qiang; Qu, Qian-Wei; Wang, Jin-Peng; Bai, Jing-Wen; Bello-Onaghise, God'spower; Li, Yu-Ang; Zhou, Yong-Hui; Chen, Xing-Ru; Liu, Xin; Zheng, Si-Di; Xing, Xiao-Xu; Eliphaz, Nsabimana; et al. (Frontiers in Chemistry, 2019)
Glutamine synthetase (GS), which catalyzes the production of glutamine, plays essential roles for most biological growth and biofilm formation, suggesting that GS may be used as a promising target for antibacterial therapy. We asked whether a GS inhibitor could be found as an anti-infective agent of Staphylococcus xylosus (S. xylosus). Here, computational prediction followed by experimental testing was used to characterize GS. The sorafenib was finally determined through computational prediction. In vitro experiments showed that sorafenib has an inhibitory effect on the growth of S. xylosus by competitively occupying the active site of GS, and the minimum inhibitory concentration was 4 mg/L. In vivo experiments also proved that: treatment with sorafenib significantly reduced the levels of TNF-α and IL-6 in breast tissue from mice mastitis, which was further confirmed by histopathology examination. These findings indicated that sorafenib could be utilized as an anti-infective agent for the treatment of infections caused by S. xylosus.